RELEVANSI TEORI PENDIDIKAN IBNU KHALDUN TERHADAP PEMBENTUKAN AKHLAK DALAM PENDIDIKAN ISLAM KONTEMPORER - Irfa Afrini; Rhafdian Putra (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2025)
The moral crisis affecting modern society, particularly the younger generation, poses a significant challenge for contemporary Islamic education. This article aims to examine the relevance of Ibn Khaldun’s educational thought in shaping moral character within the framework of modern Islamic education. Using a qualitative approach through library research, this study explores the Islamic concept of morality and Ibn Khaldun's view of education, which emphasizes not only the transfer of knowledge but also the formation of character. Ibn Khaldun advocates for a holistic education—encompassing intellectual, social, and spiritual dimensions—to develop individuals with noble character. The study finds that Ibn Khaldun’s ideas are highly relevant for addressing today’s moral crisis by promoting values such as honesty, justice, and responsibility in a balanced approach between worldly and spiritual aspects.